Immunological assessment of mice hyperimmunized with native and Cobalt-60-irradiated Bothrops venoms - Ferreira Junior, R. S. [UNESP]; Nascimento, N.; Martinez, J. C. [UNESP]; Alves, J. B.; Meira, D. A. [UNESP]; Barraviera, B. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
ELISA was used to evaluate, accompany, and compare the humoral immune response of Swiss mice during hyperimmunization with native and Cobalt-60-irradiated (60Co) venoms of Bothrops jararaca, Bothrops jararacussu and Bothrops moojeni. Potency and neutralization were evaluated by in vitro challenges. After hyperimmunization, immunity was observed by in vivo challenge, and the side effects were assessed. The animals immunization with one LD50 of each venom occurred on days 1, 15, 21, 30, and 45, when blood samples were collected; challenges happened on the 60th day. Results showed that ELISA was efficient in evaluating, accompanying and comparing mouse immune response during hyperimmunization. Serum titers produced with natural venom were similar to those produced with irradiated venom. Immunogenic capacity was maintained after 60Co-irradiation. The sera produced with native venom showed neutralizing potency and capacity similar to those of the sera produced with irradiated venom. All antibodies were able to neutralize five LD50 from these venoms. Clinical alterations were minimum during hyperimmunization with irradiated venom, however, necrosis and death occurred in animals inoculated with native venom.
Keywords: venom; irradiation; Bothrops; ELISA; serum production; detoxification